Best Practice Layer 2 Security for remote Vocational Education - Priambodo, Dimas Febriyan; Syamsiah, Nurul; Setiawan, Hermawan; Yulandi (Future Science, 2021)
Open standards especially OSI are built to separate each layer and work without knowledge of each other. This concept also means if one layer is hacked, communication is compromised without another layer alert. In best practice, layer 2 security is underrated as it is considered that security has been built through the application layer. In vocational education who are prepared to work directly in the real world, should not be forgotten to be taught. This method proposed online education for teaching layer 2 security with HyperV virtual machine to build attack and defend scenarios. Hyper V is used because windows have been installed in almost all students. In Defcon was also used HyperV was found to be able to operate to respond to attack scenarios in the second layer of security. This system was implemented in 20 students (all population in class) of security engineering in the polytechnic XYZ and shows a significant increase with normal data in statistical approach with t-test. This approach causes an increase in student scores by 12.307% by implementing a new system.